1995
DOI: 10.1164/ajrccm.152.4.7551380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking cessation on airway inflammation in chronic bronchitis.

Abstract: To investigate the effect of smoking cessation on the airway inflammatory process present in nonatopic subjects with chronic bronchitis, we obtained bronchial biopsies from nine current smokers and seven exsmokers, all with symptoms of chronic bronchitis at the time of the study, and from seven healthy nonsmoking subjects. The exsmokers had stopped smoking on average 13 yr before the study, yet cough and production of sputum had persisted. Bronchial biopsies were assessed using immunohistochemical techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
3
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(137 citation statements)
references
References 25 publications
14
115
3
5
Order By: Relevance
“…This suggests an ongoing inflammatory process in the airways, in agreement with cross-sectional studies in smokers and exsmokers with COPD [3,4,9]. The presented sputum data also suggests that inflammation continues and even increases after smoking cessation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests an ongoing inflammatory process in the airways, in agreement with cross-sectional studies in smokers and exsmokers with COPD [3,4,9]. The presented sputum data also suggests that inflammation continues and even increases after smoking cessation.…”
Section: Discussionsupporting
confidence: 89%
“…Airway inflammation in bronchial biopsies and sputum did not differ between smokers and ex-smokers, except for some cytokines (interleukin (IL)-8, IL-6, soluble tumour necrosis factor-receptor (sTNF-R)75 and sTNF-R55) [3][4][5][6][7][8]. Furthermore, RUTGERS et al [9] showed that airway inflammation was more extensive in ex-smokers with COPD than in healthy ex-smokers.…”
mentioning
confidence: 98%
“…It is an independent risk factor for all cause mortality both in COPD (38), and in subjects with normal lung function, even when smoking has been accounted for (38)(39)(40). The overall ten year mortality following a diagnosis of chronic bronchitis is 50%, with respiratory failure following an acute exacerbation being the most frequent terminal event (41). Currently there are no clearly identified genetic risk factors for Chronic Bronchitis, however, twin studies have suggested that the heritability estimate for this condition is 40%, with only 14% of genetic influences shared with those related to smoking habits (42).…”
Section: Sputum Characteristicsmentioning
confidence: 99%
“…Immunohistochemical expression of ICAM-1 is significantly increased in peripheral pulmonary vessels of smokers compared with nonsmokers. 24,25 Experimental studies using cigarette smoke condensate indicate an increase in adherence of human monocytes to cultured endothelial cells, concomitantly with enhanced expression of ICAM-1 and ELAM-1. 26 Our results with regard to cigarette consumption reinforce the concept that the detrimental effects of smoking may be mediated, in part, by expression of adhesion molecules.…”
Section: Rohde Et Al Sicam-1 and Cardiovascular Risk Factorsmentioning
confidence: 99%